Confusing terminology stunts the growth of cyber insurance. Issue 4 (April 2019) - Hare-Brown, Neil
Abstract : The lack of standard terminology in cyber insurance policies causes confusion for brokers and customers and is ultimately stunting market growth. And while demand for cyber insurance is growing, the confusion about the policies available, the cover provided and the differing approaches by insurers are deterring many clients.